WEIGHTED NORLUND-EULER A-STATISTICAL CONVERGENCE FOR SEQUENCES OF POSITIVE LINEAR OPERATORS - Hoxha, Elida; Aljimi, Ekrem; Loku, Valdete (Matematichki Bilten, 2014)
We introduce the notion of weighted Norlund–Euler A-Statistical Convergence of a sequence, where A represents the nonnegative regular matrix. We also prove the Korovkin approximation theorem by using the notion of weighted Norlund-Euler A-statistical convergence. Further, we give a rate of weighted Norlund-Euler A-statistical convergence.